HUBUNGAN EFIKASI DIRI DENGAN KEPATUHAN MELAKUKAN LATIHAN FISIK PADA PASIEN DIABETES MELLITUS TIPE 2 DI RUMAH SAKIT UMUM DAERAH ARGAMAKMUR KABUPATEN BENGKULU UTARA - Hastuti Widiarti; Veby Fransisca Rozi; Devi Cynthia Dewi (Politeknik Kesehatan Kemenkes Bengkulu, 2022)
Problem : Physical exercise program in patients with diabetes mellitus has a beneficial effect on glycemic control compared to other types of physical exercise. The formulation of the problem in this study is an increase in patients with type 2 diabetes mellitus and those who have uncontrolled blood sugar levels who do not comply with physical exercise at Argamakmur General Hospital. The AimOf The Research: The purpose of this study was to determine the relationship between self-efficacy and adherence to physical exercise in patients with type 2 diabetes mellitus at the Argamakmur Regional General Hospital, North Bengkulu Regency. Research Method: uses descriptive correlation using a cross sectional approach. The research sample was 50 people with random sampling technique. The study was conducted on 30 May – 20 June 2022 at the Argamakmur Regional General Hospital, North Bengkulu Regency. Data analysis is univariate and bivariate analysis with chi-square statistical test. The results: showed that almost half of the respondents (34.0%) had poor self-efficacy and almost half of the respondents (34.0%) were not obedient in doing physical exercise at the Argamakmur General Hospital, North Bengkulu Regency with a p value of 0.019. The conclusion is that there is a relationship between self-efficacy and adherence to physical exercise in patients with Type 2 diabetes mellitus at the Argamakmur General Hospital, North Bengkulu Regency. Conclusion: Suggestions are expected to provide more education about the benefits of routine physical exercise for people with diabetes mellitus. Keywords: Diabetes Mellitus, Self-Efficacy, Physical Exercise